Web-Based Communication of Socially Responsible Activities by Gambling Operators - Tetrevova, Libena; Patak, Michal (Journal of gambling studies, 2019)
Application of the concept of corporate social responsibility (CSR) is of fundamental importance for the future existence and success of gambling operators, the activity of which is linked to a risk of addiction to gambling together with the negative impacts of this on the health and wellbeing of gamblers, families and society as a whole. Gambling operators must apply and effectively communicate socially responsible activities in the economic, environmental, ethical, social and philanthropic fields and in particular in the field of responsible gambling. Nowadays, it is necessary to ensure communication via modern channels in the form of corporate websites and social networks. This study evaluates the level of web-based CSR communication by gambling operators which operate in one of the post-communist countries-the Czech Republic (114 companies). It at the same time provides an alternative method of evaluating the level of CSR communication by gambling operators which makes it possible to uncover weaknesses and room for improvement on the part of the gambling operator's CSR communication practices. The results of the study show that the level of web-based CSR communication of gambling operators operating in the Czech Republic is low, both in comparison with controversial companies and also with non-controversial companies. Economic responsibility activities, responsible gambling and philanthropic responsibility activities are communicated to the greatest extent. On the contrary, ethical responsibility activities are communicated the least.
Keywords: dospělí; návykové chování; organizační kultura; Humans; Behavior, Addictive; Social Responsibility; veřejná politika; Czech Republic; Public Policy; sociální chování; Česká republika; Corporate social responsibility; Organizational Culture; sociální odpovědnost; Internet; Adult; Social Behavior; internet; Responsible gambling; lidé; Gambling operators; Gambling; Web-based communication; hráčství